Rancang Bangun Sistem Informasi Akademik SMP YLPP Palembang Berbasis Web - Evi Yulianingsih; Iin Seprina (Jurnal Ilmiah Matrik, 2022)
Abstract :The rapid development of information systems has a major influence, especially in the world of education Academic Information System is the most important part to introduce and facilitate the school in carrying out all activities. SMP YLPP Palembang is a junior high school which is currently not equipped with information technology that can manage academic data from recording teacher, student and grade data, some still use written document processing in a ledger (a book prepared to record all grades based on class and year). active teaching) which is then archived by the academic section. The subject teacher processes grades on a special assessment sheet and then submits it to the homeroom concerned, daily attendance is carried out on the attendance sheet which at the end of the semester is recapitulated by the homeroom teacher, violations committed by students are recorded in the violation book with sanctions based on certain points causing difficulty in presenting information if needed at any time, a Web-based Information System will be built using the Web Engineering method with stages consisting of Communication, Planning, Modeling, Constructions, and Deployment, by building an Information System in the future it will improve the data processing system at SMP YLPP Keywords: Academic Information System, Design, Web, Web Engineering